2009
DOI: 10.1021/ja9024885
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Brønsted Acid-Catalyzed N-Acyliminium Cyclization Cascades

Abstract: An enantioselective Brønsted acid-catalyzed N-acyliminium cyclization cascade of tryptamines with enol lactones to form architecturally complex heterocycles in high enantiomeric excess has been developed. The reaction is technically simple to perform as well as atom-efficient and may be coupled to a gold(I)-catalyzed cycloisomerization of alkynoic acids whereby the key enol lactone reaction partner is generated in situ. Employing up to 10 mol % bulky chiral phosphoric acid catalysts in boiling toluene allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
170
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(184 citation statements)
references
References 38 publications
4
170
0
10
Order By: Relevance
“…Both protein-binding frequencies and selectivities are increased among compounds having: (i) increased content of sp 3 -hybridized atoms relative to commercial compounds, and (ii) intermediate frequency of stereogenic elements relative to commercial (low frequency) and natural (high frequency) compounds. Encouragingly, these favorable structural features are increasingly accessible using modern advances in the methods of organic synthesis (21)(22)(23)(24)(25)(26) and commonly targeted by academic organic chemists as judged by the compounds used in this study that were contributed by 6. Analysis of binding promiscuity among hit compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Both protein-binding frequencies and selectivities are increased among compounds having: (i) increased content of sp 3 -hybridized atoms relative to commercial compounds, and (ii) intermediate frequency of stereogenic elements relative to commercial (low frequency) and natural (high frequency) compounds. Encouragingly, these favorable structural features are increasingly accessible using modern advances in the methods of organic synthesis (21)(22)(23)(24)(25)(26) and commonly targeted by academic organic chemists as judged by the compounds used in this study that were contributed by 6. Analysis of binding promiscuity among hit compounds.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is clearly in contradiction with previously reported works in which amine catalysts were compatible with gold catalysts. [40][41][42][43][44] Indeed, in our case, it seems that the acid prevents the deactivation of the gold catalyst, by interacting with the amine organocatalyst. The amount of p-TsOH should be at least the same as the one of diphenylprolinol silyl ether V so that the reaction can occur (entry 2, Table 8).…”
Section: Nitroenynesmentioning
confidence: 94%
“…[40] Dixon also documented an Au(I) and chiral Brønsted acid multicatalyst cascade in the enantioselective cyclization cascade. [41] Gong reported that the gold catalysis and Brønsted acid catalysis are compatible in the gold-catalyzed hydroamination and transfer hydrogenation. [42] However, those works refer to dual or cooperative catalysis.…”
Section: Nitroenynesmentioning
confidence: 99%
“…In the past, organocatalysts exhibiting weak metal-coordination abilities have successfully been combined with transition metal catalysis in elegant reactions. A relatively well-studied system in this direction includes a combined use of a transition metal (such as gold, palladium, iridium, ruthenium) catalyst with chiral amine or phosphoric acid catalysts [7][8][9][10][11][12][13][14] . In contrast, the combined use of N-heterocyclic carbenes(NHCs) as organocatalysts [15][16][17][18] that can likely behave as strong-coordinating ligands [19][20][21][22] with transition metal catalysts remains challenging.…”
mentioning
confidence: 99%